Corneal topographic changes after 20-gauge pars plana vitrectomy associated with scleral buckling for the treatment of rhegmatogenous retinal detachment - Grandinetti,Alexandre Achille (2013)
PURPOSE: To evaluate the changes in corneal topography after 20-gauge pars plana vitrectomy associated with scleral buckling for the repair of rhegmatogenous retinal detachment. METHODS: Twenty-five eyes of 25 patients with rhegmatogenous retinal detachment were included in this study. 20-gauge pars plana vitrectomy associated with scleral buckling was performed in all patients. The corneal topography of each was measured before surgery and one week, one month, and three months after surgery by computer-assisted videokeratoscopy. RESULTS: A statistically significant central corneal steepening (average, 0,9 D , p<0,001) was noted one week after surgery. The total corneal astigmatism had a significant increase in the first postoperative month (p=0,007). All these topographic changes persisted for the first month but returned to preoperative values three months after the surgery. CONCLUSION: Pars plana vitrectomy with scleral buckling was found to induce transient changes in corneal topography.